Comparision of staining methods for two dimensional electrophoresis gel resolved with Puntius javanicus liver proteome - Mohd Khalizan Sabullah; Siti Aqlima Ahmad; Fisal Ahmad; Siti Aimi Sarah Zainal Abidin; Azlan Jualang Gansau; Mohd Rosni Sulaiman (hibiscus publisher, 2014)
The aim of this study was to compare the various staining methods based on commassie briliant blue and silver nitrate stain for the two dimensional gel electrophoresis resolved with Puntius javanicus liver proteome. The staining methods were selected base on the previous report about their compatibility with the mass spectrometry analysis. Silver staining method is known as the most sensitive method to visualize the maximum number of protein spots resolved in 2D gel but it is less sensitive(incompatible) toward mass spectrometry detection. Results of this study showed that a modified staining method using colloidal coomassie blue G-250 (CCB) is roughly similarly sensitive but lower protein spot detected compared with silver staining (SS) as indicated at the number of 303±26 and 693±14of protein resolved in both types of stained gels. The conventional methods of staining using commassie brilliant blue G-250 and R-250 only detected less number of protein spots(128±17and 78±11, respectively) compared to modified CCB staining method. As the commasie brilliant blue stain wasis known to be a very sensitive for mass spectrometry detection, the modified method of CCB was selected for further study on Puntius javanicus liver proteome.